Мифологическая пародия. Правитель и шут - Казымоглу, Мухтар (Народна творчість та етнологія, 2014)
Как известно, пародия в литературе является комическим подражанием художественному произведению или группе произведений. Мифологические пародии, проводившиеся в виде обряда, естественно, построены на юморе, и этот юмор создан на основе коллизии темы и стиля. Но в мифологических пародиях юмор не направлен на критику подражаемого. В раскрытии нюансов бинарности фигур короля и шута опозиции посуда и домовой, Году и богиня солнца (дождя), лжебогатырь и канатоходец играют вспомогательную роль. Но все они берут начало из одного мифологического источника. В статье исследован источник мифологических раздвоений. As it is known, the parody of literature is the comic imitation of a piece of art or group of arts. The mythological parody conducted as a form of ritual had been traditionally built on humour, and this humour was based on the collision of theme and style. But in mythological parody, the humour isn`t directed at the criticism of the subject of imitation. For revealing the nuances of bifurcation, the ruler and the jester, such double-faced beings as kitchen utensils and evil spirits, Godu and the goddess of the Sun (rain), false-hero and rope-dancer play the auxiliary role. But all of them take their beginning from the mythological sources. This article is dedicated to some sources of mythological bifurcation.